Naphthalimide-Based Fluorescent Polymers for Molecular Detection - Oshchepkov, Aleksandr S.; Oshchepkov, Maxim S.; Oshchepkova, Margarita V.; Al-Hamry, Ammar; Kanoun, Olfa; Kataev, Evgeny (Advanced Optical Materials, 2021)
The beginning of the 21st century was marked by the intensive development of fiber-optic sensors. New functional materials with excellent sensory properties are required to design such sensors. Fluorescent probes for neutral and charged molecules are constantly developing. However, only a small part of the reported probes was successfully converted into functional sensing polymers and found real-world applications. A great challenge is to retain the sensing properties of a probe in a polymer matrix. The purpose of this review is to understand how properties of a probe are changed upon incorporation into a polymer and to reveal successful approaches. The review focuses on the use of the naphthalimide-based probes in the construction of sensing polymers. The literature overview is presented according to the nature of the guest molecules targeted for the quantitative detection: cations, anions, and small organic molecules.
CRIS-Team Scopus Importer:2021-02-26
Keywords: fiber-optic sensor; fluorescence; fluorescent polymer; molecular probe; naphthalimide